2016
DOI: 10.1371/journal.pone.0161010
|View full text |Cite
|
Sign up to set email alerts
|

The Shift of ERG B-Wave Induced by Hours' Dark Exposure in Rodents

Abstract: PurposeDark adaptation can induce a rapid functional shift in the retina, and after that, the retinal function is believed to remain stable during the continuous dark exposure. However, we found that electroretinograms (ERG) b-waves gradually shifted during 24 hours’ dark exposure in rodents. Detailed experiments were designed to explore this non-classical dark adaptation.MethodsIn vivo ERG recording in adult and developing rodents after light manipulations.ResultsWe revealed a five-fold decrease in ERG b-wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
3
2
1
Order By: Relevance
“…In agreement with previous studies in rodents [26,29,33], canines [25] and humans [20], we demonstrated that the implicit times of the flash ERGs decreased during light adaptation as well as during dark adaption. As proposed above for their corresponding amplitudes, the sudden increase after background light onset and subsequent decrease in implicit times over both light/dark adaptation periods is probably also a general recovery after an instantaneous change in implicit time following the alteration in adaptation level.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies in rodents [26,29,33], canines [25] and humans [20], we demonstrated that the implicit times of the flash ERGs decreased during light adaptation as well as during dark adaption. As proposed above for their corresponding amplitudes, the sudden increase after background light onset and subsequent decrease in implicit times over both light/dark adaptation periods is probably also a general recovery after an instantaneous change in implicit time following the alteration in adaptation level.…”
Section: Discussionsupporting
confidence: 93%
“…Although there are studies that describe the changes in cone or rod ERGs after bleaching of the retina using paired flash stimuli [30,31,32], there are not many data about ERG responsivity changes during dark adaptation that are recorded with single flash ERGs or flicker ERGs. Li et al [33] found an increase in amplitude and a decrease in latency in rodents during dark adaptation, which is similar to the results in the study of Maehara et al [25] in canines.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mERG was conducted using the multi-electrode array (MEA) recording system (USB-MEA60-Up-System, MultiChannel Systems, Germany) with the standard 8x8 probe (60MEA200/30iR-Ti-gr) as previously described (Iraha et al, 2018). In order to distinguish the effects of prolonged dark adaptation from dark rearing, mice reared under LD and LL conditions were dark adapted for 24 h prior to the recording, as long dark adaptation (6 to 24 h) can significantly reduce the b-wave amplitude (Li et al, 2016). P14 B6J mice were deeply anesthetized with sevoflurane inhalation, followed immediately by decerebration and harvest of retinas.…”
Section: Methodsmentioning
confidence: 99%
“…Electroretinogram recordings from mice and rats indicate that light- and dark-adaptation occur not only in photoreceptor outer segments, but also at photoreceptor synapses ( 6 , 7 ). Additionally, electrophysiological studies using genetically-modified mice, in which key steps in retinal processing are inactivated, point to photoreceptor to ON-BC transmission as an important site of light-adaptation synaptic plasticity ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%